Teacher-Student Interaction: A Strong Foundation for Quality Character Education - Dewi Purnama Sari; Sutarto Sutarto (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Character education is critical in developing studentsÔÇÖ attitudes and personalities. One approach that can be used is through teacher interaction with students. This study aims to reveal teachersÔÇÖ approach to interacting with students to develop good character values. This study is a qualitative study with a phenomenological approach. The research informants were eight teachers who intensively interacted with students for over a year. The data collection technique used in-depth interviews. The data analysis technique used was interpretative phenomenological analysis (AFI), which includes three stages: horizontalization, developing meaning units, and presenting the phenomenonÔÇÖs essence. To obtain valid data, researchers conducted source triangulation. The study results showed that intensive teacher-student interaction, both classically and individually, can provide understanding and foster studentsÔÇÖ awareness of having good character. Therefore, to build studentsÔÇÖ character in a better direction, teachers are strongly advised to constantly interact with students intensively, both classically and individually, to foster sensitivity and studentsÔÇÖ means of having good character.